2017
DOI: 10.1038/nature24035
|View full text |Cite
|
Sign up to set email alerts
|

Structure of mammalian endolysosomal TRPML1 channel in nanodiscs

Abstract: Transient receptor potential mucolipin 1 (TRPML1) is an endo/lysosomal cation channel ubiquitously expressed in mammalian cells1,2 and its loss-of-function mutations are the direct cause of Type IV mucolipidosis (MLIV), an autosomal recessive lysosomal storage disease3-6. Here we present the single particle cryo-electron microscopy (cryo-EM) structure of the mouse TRPML1 channel embedded in nanodiscs. Combined with mutagenesis, the TRPML1 structure reveals that phosphatidylinositol bisphosphate (PIP2) binds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
170
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(183 citation statements)
references
References 43 publications
(55 reference statements)
5
170
0
Order By: Relevance
“…Previous studies have shown that there is a PtdIns(3,5)P 2 -binding site in the positively charged pre-S1 region of TRPML1 15 , which is distant from the ML-SA1-binding site that we mapped in the membrane domain. A related Nature paper provides specific insights into TRPML1 in the lipid environment 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there is a PtdIns(3,5)P 2 -binding site in the positively charged pre-S1 region of TRPML1 15 , which is distant from the ML-SA1-binding site that we mapped in the membrane domain. A related Nature paper provides specific insights into TRPML1 in the lipid environment 42 .…”
Section: Discussionmentioning
confidence: 99%
“…1C, D) reminiscent of many tetrameric voltage-gated cation channels, and all other TRP channels to date (713). hTRPM4 has additional membrane embedded fragments that surround the S1–S4 domain from the inner leaflet of the membrane (Fig.…”
mentioning
confidence: 99%
“…[2] Grapheneo xide (GO) has been the most frequently employed derivativeo fg raphene for developing such membranes, owing to its abundant oxygenated groups, [3] which enable its dispersion in water and greatly improvet he possibilities for assembly of membrane nanostructures, including laminates and hybrids. [10] Nevertheless, the efficient rejection of ions through the cation-controlled GO membranes relied on aqueous solutionsc ontaining cations that are not often presenti na pplicationsf or processes such as solvent dehydration or gas separation. Strategies involving covalent bonding, [6] hydrogen bonding, [7] electrostatic attraction, [8] and chemicalr eduction [9] have been designed to enhance the structural stabilityo fG O membranes.…”
mentioning
confidence: 99%
“…[10] Nevertheless, the efficient rejection of ions through the cation-controlled GO membranes relied on aqueous solutionsc ontaining cations that are not often presenti na pplicationsf or processes such as solvent dehydration or gas separation. The resulting cation-controlled GO membranes exhibited excellent ion-sieving properties to effect water desalination.…”
mentioning
confidence: 99%